The application of computed tomography in wound ballistics research. (August 2015) - Tsiatis, Nick; Moraitis, Konstantinos; Papadodima, Stavroula; Spiliopoulou, Chara; Kelekis, Alexis; Kelesis, Christos; Efstathopoulos, Efstathios; Kordolaimi, Sofia; Ploussi, Agapi
Abstract: In wound ballistics research there is a relationship between the data that characterize a bullet and the injury resulted after shooting when it perforates the human body. The bullet path in the human body following skin perforation as well as the damaging effect cannot always be predictable as they depend on various factors such as the bullet's characteristics (velocity, distance, type of firearm and so on) and the tissue types that the bullet passes through. The purpose of this presentation is to highlight the contribution of Computed Tomography (CT) in wound ballistics research. Using CT technology and studying virtual "slices" of specific areas on scanned human bodies, allows the evaluation of density and thickness of the skin, the subcutaneous tissue, the muscles, the vital organs and the bones. Density data taken from Hounsfield units can be converted in g/ml by using the appropriate software. By evaluating the results of this study, the anatomy of the human body utilizing ballistic gel will be reproduced in order to simulate the path that a bullet follows. The biophysical analysis in wound ballistics provides another application of CT technology, which is commonly used for diagnostic and therapeutic purposes in various medical disciplines.